Philippines equity report: Investment case for financing equitable progress towards MDGs 4 and 5 in the Asia-Pacific region - Aleli Kraft; Paul Mariano; Samuel Kault; Eliana Jimenez-Soto; Kim-Huong Nguyen (University of the Philippines, School of Economics (UPSE), 2011)
A lack of maternal, newborn and child health (MNCH) equity analysis in recent years has led to a substantive gap in the literature. Responding to this, we use the best available country data and the most advanced methods to investigate the levels and distribution of, and the trends in, both MNCH mortality and intervention coverage. The findings shed light on inequities between rural and urban populations, and between different ethnic groups, development regions and wealth quintiles. Analyses of mortality over time allow the backtrack of mortality progress, enabling the evaluation of past policies' influences on reducing health inequity and of the appropriateness of current and potential future policy. Hence, this Equity Report aims to constitute a milestone for MNCH equity analyses in the Philippines ...
Keywords: 330; Gesundheit; Kinder; Erwachsene; Millennium Development Goals; Sterblichkeit; Philippinen